Keterkaitan Antara Struktur Dan Budaya Organisasi Dengan Strategi Yang Ada Di Lembaga Pendidikan MAS Al-Washliyah 22 Tembung - Marsyeli Marsyeli; Fachri Habib; Muhammad Muflih Dermawan; Ahmad Mukhlasin (Jurnal Publikasi Ilmu Manajemen, 2024)
The relationship between organizational structure and culture and strategy in educational institutions is an important and complex topic, especially in the MAS Al-Washliyah 22 Tembung educational institution. Organizational structure determines how tasks and responsibilities are divided and coordinated within an organization, while organizational culture determines the values, norms, and behaviors accepted within the organization. Both can influence the strategies chosen by educational institutions. This research aims to identify the relationship between organizational structure and culture and existing strategies at the MAS Al-Washliyah 22 Tembung school. This research will involve participants consisting of employees and teaching staff at the school. The methods that will be used are interviews and observations to collect data about the organizational structure and culture, as well as existing strategies in the educational institution. This research found that the relationship between organizational structure and culture and strategy in educational institutions is very important to achieve the desired strategic goals. This research has important implications for leaders of educational institutions. Leaders of educational institutions need to be aware of the relationship between organizational structure and culture and their organizational strategy. In this way, leaders of educational institutions can increase the effectiveness of their organizations in achieving their goals.